Two years clinical outcomes with the state‐of‐the‐art PCI for the treatment of bifurcation lesions: A sub‐analysis of the SYNTAX II study. Issue 1 (12th August 2019) - Modolo, Rodrigo; Kogame, Norihiro; Komiyama, Hidenori; Chichareon, Ply; de Vries, Ton; Tomaniak, Mariusz; Chang, Chun Chin; Takahashi, Kuniaki; Walsh, Simon; Lesiak, Maciej; Moreno, Raul; Farrooq, Vasim; et al.
Abstract: Background: Bifurcation PCI is associated with a lower rate of procedural success, especially in multivessel disease patients. We aimed to determine the impact of bifurcation treatment on 2‐years clinical outcomes when a state‐of‐the‐art PCI strategy (heart team decision‐making using the SYNTAX score II, physiology guided coronary stenosis assessment, thin strut bioresorbable polymer drug‐eluting stent, and intravascular ultrasound guidance) is followed. Methods: Three‐vessel disease patients enrolled in the SYNTAX II trial ( n = 454) were categorized in patients with (a) ≥1 treated bifurcation ( n = 126), and (b) without bifurcation ( n = 281). The primary endpoint was the occurrence of major adverse cardio and cerebrovascular events (MACCE—a composite of all‐cause death, stroke, any myocardial infarction, or any revascularization) at 2 years. Secondary endpoints were the occurrence of target lesion failure (TLF) defined as cardiac death, target‐vessel myocardial infarction and ischemia‐driven target lesion revascularization, and the individual components of the composite primary endpoint, as well as stent thrombosis. Results: A total of 145 bifurcation were treated in 126 patients. At 2 years, MACCE occurred in 75/407 patients (20.7% for bifurcation versus 17.5% for nonbifurcation, hazard ratio [HR] of 1.28, CI95% 0.78–2.08, p = .32). TLF presented a trend toward higher occurrence in bifurcation (16.8% vs. 10.8%, HR 1.75, CI95% 0.99–3.09, p = .053). Definite stent thrombosis did not differ at 2‐year between groups (0.8% for the bifurcation vs. 0.7% for the nonbifurcation, p = .92). Conclusion: Bifurcation treatment in patients with three‐vessel disease undergoing state‐of‐the‐art PCI had similar event rate of MACCE but was associated with a trend toward higher incidence of TLF compared with nonbifurcation lesions.